Thirty-Day Hospital Readmissions for Acute Gout in the United States: Analysis of the Nationwide Readmission Database. Issue 2 (March 2022) - Kichloo, Asim; Edigin, Ehizogie; Jamal, Shakeel; El-amir, Zain; Aucar, Maria Isabel; Wani, Farah; Eseaton, Precious O.; Annapureddy, Narender; Cabling, Marven G.; Manadan, Augustine M.
Abstract : Background/Objective: The aims of this study were to describe the rates and characteristics of nonelective 30-day readmission among adult patients hospitalized for acute gout and to assess predictors of readmission. Methods: We analyzed the 2017 Nationwide Readmission Database. Gout hospitalizations were identified using the International Classification of Diseases, Tenth Revision, Clinical Modification code. Hospitalizations for adult patients were included. We excluded planned or elective readmissions. We utilized χ 2 tests to compare baseline characteristics between readmissions and index hospitalizations. We used multivariate Cox regression to identify independent predictors of readmissions. Results: A total of 11, 727 index adult hospitalizations with acute gout listed as the principal diagnosis were discharged alive and included. One thousand five hundred ninety-four (13.6%) readmissions occurred within 30 days. Acute gout was the most common reason for readmission. Readmissions had higher inpatient mortality (2.4% vs 0.1%, p < 0.0001), greater mean age (68.1 vs 67.0 years, p = 0.021), and longer hospital length of stay (5.9 vs 3.8 days, p < 0.0001) compared with index hospitalizations. Charlson Comorbidity Index scores of ≥2 (score 2: adjusted hazards ratio [AHR], 1.67; p = 0.001; score ≥3: AHR, 2.08; p < 0.0001), APR-DRG (All Patients Refined Diagnosis Related Groups) severity levels ≥2 (level 2: AHR, 1.43; p = 0.044; level 3: AHR, 1.83; p = 0.002; level 4: AHR, 2.38; p = 0.002), admission to metropolitan hospital (AHR, 1.83; p = 0.012), atrial fibrillation (AHR, 1.31; p = 0.004), and anemia (AHR, 1.30; p = 0.001) were significantly associated with 30-day readmissions. Conclusions: Acute gout readmissions were associated with worse outcomes compared with index hospitalizations. Charlson Comorbidity Index scores ≥2, APR-DRG severity levels ≥2, admission to metropolitan hospital, atrial fibrillation, and anemia were significant predictors of readmission.